Forming an Ethical Mindset: Applying Constructivist Learning to Teach Anti-Corruption Education in Junior High Schools - Luh Wayan Yasmiatti (Journal of Pedagogi, 2024)
Corruption is a widespread problem that disrupts the stability and progress of a country, including Indonesia, and undermines the economy and public trust. Education is essential to tackle corruption from an early age to foster a culture of integrity and ethical behavior. In this article, we talk about how constructivist learning theory can be used to teach anti-corruption education in junior high schools. The purpose of this study is to show how important constructivist methods such as experiential learning, value-based education, role play, and discussion are in encouraging moral reasoning and civic responsibility among young students. Recent studies on constructivist pedagogy and anti-corruption education were collected through literature review methodologies. The findings suggest that constructivism promotes deeper moral engagement and better critical thinking, which is essential for understanding and combating corrupt behavior. In addition, students internalize anti-corruption principles through real-world scenarios, discussions, and community projects. As this study shows, the constructivist approach offers a promising platform for teaching anti-corruption education because it allows students to participate in the learning process interactively and think critically. This study shows that schools should prioritize a constructivist approach in equipping students with the moral competencies necessary to build a non-corrupt society